Human immunodeficiency virus types 1 and 2 infection in some rural areas of Nigeria (1998)
The prevelence of human immunodeficiency virus types 1 and 2 in rural areas of Nigeria was estimated using 1089 sera collected in 18 locations from 1992 to early 1994. The sera were tested with Enzyme Linked Immunosorbent Assay(ELISA) and confirmed by western immunoblotting technique. Overall, 13 (1.2%) of the 1089 sera were positive for antibodies to HIV-1 and HIV-2. Prevalence of 0.6% and 0.8% were obtained for HIV-1 and HIV-2 (50.0%) were found in Zurhlrrua and Umubuzu. A seroprevalence of 1.2% was obtained for both male and female groups tested. The highest prevalence of HIV was found among individuals 30-39 years age group. An overall increase in prevalence of HIV-1 and HIV-2 infection was obtained over the three years during which samples were collected for this study (0.7% in 1992, 1.0% in 1992 and 3.4% in 1994). In addition, two sera were positive for both HIV-1 and HIV-2. The detection of antibodies to HIV-1 and HIV-2 in the rural areas where blood samples were collected for this study shows that both virus are widespread in the rural communities of Nigeria.